Patients' expectations of and experiences with psychosocial care needs in perioperative nursing: a descriptive study - Kari Ingstad; Mona K. Pedersen; Lisbeth Uhrenfeldt; Preben U. Pedersen (BMC, 2023)
Abstract Background Meeting inpatients' psychosocial care needs is essential for their wellbeing, recovery, and positive experiences. This study aimed to describe and compare surgical inpatients' subjective perceptions of the importance of fundamental psychosocial and overall care received. Methods A descriptive study with a convenient sample was conducted from September 2019 to April 2020. A total of 194 surgical inpatients from Norway and Denmark answered a perioperative user participation questionnaire on the day of discharge. The questionnaire was previously face- and content validated. The questionnaire assessed patients' sociodemographic characteristics and four dimensions of fundamental care domains: Psychosocial, Relational, Physical, and System level. This study reports the results from the psychosocial domain. Descriptive statistics including frequencies, percentages, means, and standard deviations were used to analyze background information variables. The congruency between participants' expectations of and experiences with psychosocial care is presented. Results The inpatients expected (and experienced) the healthcare personnel to treat them with respect and dignity, and to be involved and informed throughout their perioperative care. The average ratings regarding these aspects of psychosocial care needs were 72.1-93.8%. There was congruency between patients' perceptions of the subjective importance (SI) of psychosocial fundamental care and their perceived reality (PR) of care. Congruency between high SI and high PR ranged from 59.1 to 92.2%, and congruency between low SI and low PR ranged from 0 to 6.6%. Incongruency between SI and PR varied between 5.9 and 39.6% and was mainly related to higher PR than SI. We found no association between education level, sex, length of stay, age, and patient expectations of or experiences with psychosocial care needs. Conclusions Surgical inpatients in Norway and Denmark experience respectful and dignified treatment, and they feel involved and informed in their perioperative care. It is important to include patient perspectives in further research to avoid missed care and disconnection between what patients prefer and what healthcare personnel plan to do. Understanding patient preferences might also lead to less stress and workload for healthcare personnel.